1999
DOI: 10.1097/00000658-199905000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage Decreases Macrophage Inflammatory Protein 2 and Interleukin-6 Release

Abstract: Because most wound infections occur early after severe trauma, these results suggest that the dysfunction of wound exudate cells after hemorrhage might contribute to the increased incidence of wound infections. Therefore, attempts to enhance or restore wound cell immune function might be helpful for decreasing the incidence of wound infections in trauma victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Patients who were hypotensive upon admission were generally more likely to develop hospital-acquired pneumonia, wound infection and bacteremia than normotensive patients [5,7,12,13,16]. Several trials have reported a depression of both the innate and acquired immune system as a result of acute hemorrhage causing an increased susceptibility to infection, SIRS and sepsis in affected patients [15,35]. Angele et al demonstrated that wound exudate cells harvested on the first and third postoperative days from hemorrhaged animals exhibit an impaired release of proinflammatory cytokines and chemokines such as IL-1b and IL-6 in response to a second stimulus (lipopolysaccharide, LPS) in vitro [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who were hypotensive upon admission were generally more likely to develop hospital-acquired pneumonia, wound infection and bacteremia than normotensive patients [5,7,12,13,16]. Several trials have reported a depression of both the innate and acquired immune system as a result of acute hemorrhage causing an increased susceptibility to infection, SIRS and sepsis in affected patients [15,35]. Angele et al demonstrated that wound exudate cells harvested on the first and third postoperative days from hemorrhaged animals exhibit an impaired release of proinflammatory cytokines and chemokines such as IL-1b and IL-6 in response to a second stimulus (lipopolysaccharide, LPS) in vitro [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have reported a depression of both the innate and acquired immune system as a result of acute hemorrhage causing an increased susceptibility to infection, SIRS and sepsis in affected patients [15,35]. Angele et al demonstrated that wound exudate cells harvested on the first and third postoperative days from hemorrhaged animals exhibit an impaired release of proinflammatory cytokines and chemokines such as IL-1b and IL-6 in response to a second stimulus (lipopolysaccharide, LPS) in vitro [15]. They concluded that this dysfunction of wound exsudate cells could provide a potential mechanism by which to explain the impaired bacterial resistance in wounds of trauma patients, resulting in a higher rate of wound infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cytokines have been shown to be a major information transmission system in the host response to stress, a close relationship has been demonstrated between excessive reaction of pro-inflammatory cytokines and multiple organ failure [4,5]. On the other hand, in response to major stress, nonspecific immunocompetence, such as the level of circulating lymphocyte counts and macrophage activity are known to decrease [6][7][8]. Bone [9] proposed compensatory anti-inflammatory response syndrome (CARS) to describe the state of immunosuppression, as opposed to systemic inflammatory response syndrome (SIRS).…”
mentioning
confidence: 99%
“…Indeed, in this study, the number of postoperative circulating T lymphocytes significantly decreased in the control group and did not return to the preoperative values during the study period, but the decrease in the number and in the mitogenic activity of lymphocytes was significantly reduced by UTI. Moreover, the production of TNF-α in whole blood, which has been observed to decrease under stressful conditions such as invasive surgery [13], hemorrhage [14], and sepsis [15], showed an early recovery in the UTI group. These data suggest that a protease-modulating therapy may be a new strategy for dealing with postoperative immunosuppression.…”
Section: Discussionmentioning
confidence: 99%